Determinants of Auditor Turnover Moderated by Job Satisfaction at Public Accounting Firms in East Java - Grana Koeswardani; Endah Sulistyo; Rida Perwita Sari (Economics and Business Journal (ECBIS), 2026)
The present study is a statistical hypothesis testing research aimed at examining the determinants of auditor turnover intention, specifically the influence of work motivation, workload, and time budget pressure as independent variables, with job satisfaction acting as a moderating variable. The research was conducted among auditors working at Public Accounting Firms in East Java. The population of the study consisted of junior and senior auditors employed at medium- and large-scale firms operating in the region. Data were collected using a survey method through primary questionnaires and analyzed using SmartPLS 3.0 to test the structural relationships between variables. The findings of this study indicate that work motivation negatively influences turnover intention, whereas workload and time budget pressure positively influence turnover intention. The results also show that job satisfaction moderates the relationship between work motivation and turnover intention, strengthening its negative effect. However, job satisfaction does not significantly moderate the influence of workload or time budget pressure on turnover intention. Overall, the study highlights the crucial role of job satisfaction in reducing the tendency of auditors to leave their organization, especially in environments with varying levels of motivation, workload, and time pressure.